Electrical properties of vacuum-evaporated CdTe thin films - Sahay P.P.; Jha S.; Shamsuddin M. (My University, 2025)
Electrical properties of vacuum-evaporated CdTe thin films was investigated. The films were prepared by thermal evaporation technique in a vacuum and resistance was measured using Keithley Programmable Electrometer. X-ray diffraction studies showed that the films had a polycrystalline nature and belonged to the cubic system with a preferred orientation along the (111) direction. The sheet resistance was found to decrease with an increase in film thickness. The electrical behavior of the films was explained using a polycrystalline model for semiconductors.